Tinjauan Hukum Islam Terhadap Praktik Jual Beli Pupuk Dengan Pembayaran Setelah Panen (Studi Di Desa Laccori Kecamatan Dua Boccoe Kabupaten Bone) - Andi Muhammad Aidil (STAI YAPIS Takalar, 2021)
“This study aims to determine the process of buying and selling fertilizer in Laccori Village, Dua Boccoe District, Bone Regency and to find out an overview of Islamic law on the practice of buying and selling fertilizer with payment after harvest in Laccori Village, Dua Boccoe District, Bone Regency. In this study using a description method with a qualitative approach. This research was conducted by collecting data and information obtained directly from informants by observing directly. The results showed that the first sale and purchase transaction of agricultural fertilizer with payment after harvest in Laccori Village, Dua Boccoe District, Bone Regency had been carried out for a long time. Farmers will take agricultural fertilizer first and then farmers will pay for it after harvest. Fertilizer buying and selling transactions with payment after harvest in Laccori Village, Dua Boccoe District, Bone Regency are in accordance with Islamic law. There is no element of gharar, transactions are carried out voluntarily without any coercion between the seller and the buyer.” Keyword: Buying and selling, fertilizer, Islamic law